Ibnu Taimiyyah on Repentance as Eliminating the Punishment for Adultery [Taubat Sebagai Penghapus Had Zina Menurut Ibnu Taimiyyah] - Syuhada Syuhada; Zulkiram Zulkiram (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2021)
Abstract: Scholars differ on whether the repentance of an adulterer can abrogate the punishment of the limit. Some scholars state that there is no fall at all, while others state that the punishment is limited to fall. In this regard, Ibn Taymiyyah's opinion is the same as the last opinion that the repentance of an adulterer can remove the demand of the limit as long as it has not been submitted to the ruler, but if it has been submitted to the ruler then the limit does not fall so it remains punished and his repentance is accepted by Allah swt. The research method is qualitative, the type of literature research, research data from library materials in the form of books of jurisprudence, law, and other relevant literature, both from primary, secondary, and tertiary data, then analyzed by descriptive analysis. The results of the study showed that according to Ibn Taymiyyah, the perpetrator of adultery who repented before being complained to the government fell ḥadd adultery. The perpetrator does not have to admit his actions because the attitude is seen as better. As for the adulterer who repents after being complained to the government, then it does not fall ḥadd adultery. The perpetrator must still be punished, his repentance is accepted by Allah swt., while the punishment of ḥadd is a consummation of his repentance. The argument used by Ibn Taymiyyah about the fall of ḥadd zina due to repentance refers to the provisions of the QS. al-Nisā 'verse 16, QS. al-Māidah verses 33-34, QS. Ṭāhā verses 121-122, and the hadith narrated by Abū Dawud about the punishment of Maiz. The method of istinbāṭ that he uses tends to use heroic reasoning, that is, looking at the sides and rules of language, general and special relations, cause and effect, and understanding the words of the Qur'an. Abstrak: Para ulama berbeda pendapat apakah tobat seorang pezina dapat membatalkan hukuman batas? Sebagian ulama menyatakan bahwa tidak ada jatuhnya sama sekali, sedangkan sebagian lainnya menyatakan bahwa hukumannya terbatas pada jatuh. Dalam hal ini pendapat Ibnu Taimiyah sama dengan pendapat yang terakhir bahwa tobat seorang pezina dapat menghilangkan tuntutan batas selama belum diserahkan kepada penguasa, tetapi jika sudah diserahkan kepada penguasa maka batasnya tidak jatuh sehingga tetap dihukum dan tobatnya diterima oleh Allah SWT. Adapun metode penelitiannya adalah kualitatif, jenis penelitian kepustakaan, data penelitian dari bahan pustaka berupa buku-buku fiqih, hukum, dan kepustakaan lain yang relevan kemudian data-data yang telah terkumpul, baik dari data primer, sekunder, maupun tersier. Kemudian dianalisis secara deskriptif-analisis. Hasil penelitian menunjukkan bahwa menurut Ibnu Taimiyah, pelaku zina yang bertobat sebelum mengadu ke pemerintah, jatuh hadd zina. Pelaku tidak harus mengakui perbuatannya karena sikapnya dipandang lebih baik. Adapun pezina yang bertobat setelah diadukan kepada pemerintah, maka tidak termasuk zina. Pelaku tetap harus dihukum, tobatnya diterima oleh Allah SWT., sedangkan hukuman hadd sebagai penyempurnaan tobatnya. Dalil yang digunakan Ibnu Taimiyah tentang jatuhnya hadd zina karena taubat mengacu pada ketentuan QS. al-Nisā' ayat 16, QS. al-Maidah ayat 33-34, QS. Thāhā ayat 121-122, dan hadis yang diriwayatkan oleh Abu Dawud tentang hukuman Maiz. Metode istinbāṭ yang digunakannya cenderung menggunakan nalar heroik, yaitu melihat sisi dan kaidah kebahasaan, hubungan umum dan khusus, sebab akibat, dan memahami kata-kata Alquran.